An integrative therapy for paraplegia dog with ehrlichiosis - Frizky Amelia; Danny Umbu T. Hambandima; Erly Rizka Adistya; Roro Soesatyoratih; Leni Maylina; Nindya Dwi Utami; Tatang Cahyono; Deni Noviana (ARSHI Veterinary Letters, 2019)
An eight-months-old male Golden Retriever was referred to Veterinary Teaching Hospitalof IPB University with clinical signs of non-ambulatory paraplegia, tail paralysis, urinary and faecal incontinence, pale mucosa, and loss of sensory and motoric responses on both pelvic limbs. The hematology examination showed thrombocytopenia (125x103/µL), monocytopenia (0.09x103/µL),and no significant decreased of hematocrit (36.88%). Rapid diagnostic test and blood smears were positive for Ehrlichiacanis infection. Abdominalsonogram showed splenomegaly and hepatomegaly with hepatic vessels dilatation. An integrative therapy was done using medications (vitamin B-complex, cyproheptadine, methylprednisolone, doxycycline, and Fundamin E®), herbal (Gui Pi Tang® and Fu Fang Ejiao Jiang®), acupuncture, micro-radar, and Tuina massage. The dog was able to walk and run after 10th session of the intensivetreatment then discharged from the hospital after two months. One week after, the dog started dragging his toe. A customized shoe then made to prevent furtherinjury to the affected limb. The acupuncture was continued once a week for the following two months. The dog is still able to walk and run at his last visit 5 months later. This shows that an integrative therapycan give a good performance in recovering ambulation of paraplegia dog with ehrlichiosis